Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Role of ligands in the formation, phase stabilization, structural and magnetic properties of alpha-Fe2O3 nanoparticles - Joshi, Satyawati S.; Patil, Prajakta R.; Nimase, Madhav S.; Bakare, P. P. (Journal of Nanoparticle Research, 2006)
The electrochemical synthesis of alpha Fe2O3 nanoparticles was performed using quaternary ammonium salts viz. TPAB, TBAB and TOAB in an organic medium by optimizing current density and molar concentration of the ligand. The role of ligands in the formation of alpha phase, structure and magnetic properties was investigated in details. The effect of increasing chain length on the particle size confirmed that as the chain length increases from propyl to octyl, the particle size decreases. X-ray diffraction spectra of as prepared samples and TEM analysis confirmed the amorphous nature of iron oxide. TEM showed beads of iron oxide joined together with a size distribution in the range of 6-30 nm. The Mossbauer studies also support this observation that for the lowest particle size, the line width is broader which successively reduces with increase in particle size. Iron oxide capped with TOAB indicated superparamagnetic nature at room temperature. The resultant internal magnetic field of 506 mm/s due to hyperfine splitting clearly established the formation of alpha-Fe2O3 The infrared spectroscopy and pH measurements revealed the binding of tetra alkyl ligand with iron oxide. The IR spectra and the increase in basicity of as prepared samples confirmed the formation of hydrated iron oxide. Above 800 degrees C the spectra indicated only iron oxide. Surface area obtained by BET method was 205 m(2)/g.
Keywords: Alkyl chain length; alpha-Fe2O3; Electrochemistry; magnetic properties; Nanoparticles; narrow size distribution

3D Hexaporous carbon assembled from single-layer graphene as high performance supercapacitor - Yadav, Prasad; Banerjee, Abhik; Unni, Sreekuttan; Jog, Jyoti Prakash; Kurungot, Sreekumar; Ogale, Satishchandra (Chemsuschem, 2012)
Keywords: Electrochemistry; Energy storage; graphene; porous materials; Supercapacitors

Porous-organic-framework-templated nitrogen-rich porous carbon as a more proficient electrocatalyst than Pt/C for the electrochemical reduction of oxygen - Pachfule, Pradip; Dhavale, Vishal M.; Kandambeth, Sharath; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Porous nitrogen-rich carbon (POF-C-1000) that was synthesized by using a porous organic framework (POF) as a self-sacrificing host template in a nanocasting process possessed a high degree of graphitization in an ordered structural arrangement with large domains and well-ordered arrays of carbon sheets. POF-C-1000 exhibits favorable electrocatalytic activity for the oxygen-reduction reaction (ORR) with a clear positive shift of about 40 mV in the onset potential compared to that of a traditional, commercially available Pt/C catalyst. In addition, irrespective of its moderate surface area (785 m2?g-1), POF-C-1000 showed a reasonable H2 adsorption of 1.6 wt?% (77 K) and a CO2 uptake of 3.5 mmol?g-1 (273 K).
Keywords: Adsorption; Electrochemistry; fuel cells; oxygen-reduction reaction; porous organic frameworks

Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

Sequential electrochemical unzipping of single-walled carbon nanotubes to graphene ribbons revealed by in situ Raman spectroscopy and imaging - John, Robin; Shinde, Dhanraj B.; Liu, Lili; Ding, Feng; Xu, Zhiping; Vijayan, Cherianath; Pillai, Vijayamohanan K.; Pradeep, Thalappil (ACS Nano, 2014)
We report an in situ Raman spectroscopic and microscopic investigation of the electrochemical unzipping of single-walled carbon nanotubes (SWNTs). Observations of the radial breathing modes (RBMs) using Raman spectral mapping reveal that metallic SWNTs are opened up rapidly followed by gradual unzipping of semiconducting SWNTs. Consideration of the resonant Raman scattering theory suggests that two metallic SWNTs with chiralities (10,4) and (12, 0) get unzipped first at a lower electrode potential (036 V) followed by the gradual unzipping of another two metallic tubes, (9, 3) and (10, 1), at a relatively higher potential (1.16 V). The semiconducting SWNTs with chiralities (11, 7) and (12, 5), however, get open up gradually at +/- 1.66 V. A rapid decrease followed by a subsequent gradual decrease in the metallicity of the SWNT ensemble as revealed from a remarkable variation of the peak width of the G band complies well with the variations of RBM. Cyclic voltammetry also gives direct evidence for unzipping in terms of improved capacitance after oxidation followed by more important removal of oxygen functionalities during the reduction step, as reflected in subtle changes of the morphology confirming the formation of graphene nanoribbons. The density functional-based tight binding calculations show additional dependence of chirality and diameter of nanotubes on the epoxide binding energies, which is in agreement with the Raman spectroscopic results and suggests a possible mechanism of unzipping determined by combined effects of the structural characteristics of SWNTs and applied field.
Keywords: density functional-based tight binding calculations; Electrochemistry; graphene; Raman spectral mapping; single-walled carbon nanotubes

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Multifunctional polyaniline-tin oxide (PANI-SnO2) nanocomposite: synthesis, electrochemical, and field emission investigations - Patil, Sandip S.; Harpale, Kashmira V.; Koiry, Shankar P.; Patil, Kashinath R.; Aswal, Dinesh K.; More, Mahendra A. (Journal of Applied Polymer Science, 2015)
Synthesis of PANI-SnO2 nanocomposite has been performed using a simple two step chemical oxidative polymerization route. The structural, morphological and chemical properties of the as-synthesized PANI-SnO2 nanocomposite have been revealed by various characterization techniques such as SEM, TEM, XRD, FTIR, and XPS. Interestingly the as-synthesized PANI-SnO2 nanocomposite exhibits supercapacitance value of 721 F g(-1) with energy density 64 Wh kg(-1), which is noticed to be higher than that of pristine SnO2 and PANI nanostructures. Furthermore, the galvanostatic charge-discharge characteristics revealed pseudocapacitive nature of the PANI-SnO2 nanocomposite. The estimated values of charge transfer resistance and series resistance estimated from the Nyquist plot are found to be lower. Along with the supercapacitive nature, PANI-SnO2 nanocomposite showed promising field emission behavior. The threshold field, required to draw emission current density of 1 A/cm(2), is observed to be 0.90 V/m and emission current density of 1.2 mA/cm(2) has been drawn at applied field of approximate to 2.6 V/m. The emission current stability investigated at preset values of 0.02 and 0.1 mA/cm(2) is observed to be fairly stable over duration of more than 3 h. The enhanced supercapacitance values, as well as, the promising field emission characteristics are attributed to the synergic effect of SnO2 nanoparticles and PANI nanotubes. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41401.
Keywords: conducting polymers; Electrochemistry; nanostructured polymers; surfaces and interfaces

Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation

Glycine-induced electrodeposition of nanostructured cobalt hydroxide: a bifunctional catalyst for overall water splitting - Shilpa, Nagaraju; Nadeema, Ayasha; Kurungot, Sreekumar (ChemSusChem, 2019)
Herein, an interconnected alpha-Co(OH)(2) structure with a network-like architecture was used as a bifunctional electrocatalyst for the overall water splitting reaction in alkaline medium. The complexing ability of glycine with a transition metal was exploited to form [Co(gly)(3)](-) dispersion at pH 10, which was used for the electrodeposition. High-resolution TEM, UV/Vis-diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy were used to confirm that the as-synthesized materials had an alpha-Co(OH)(2) phase. The electrocatalytic oxygen and hydrogen evolution activity of the glycine-coordinated alpha-Co(OH)(2) was found to be approximately 320 and 145 mV, respectively, at 10 mA cm(-2). The material required approximately 1.60 V (vs. reversible hydrogen electrode; RHE) to achieve the benchmark of 10 mA cm(-2) for overall water splitting with a mass activity of approximately 63.7 A g(-1) at 1.60 V (vs. RHE). The chronoamperometric response was measured to evidence the stability of the material for overall water splitting for up to 24 h. Characterization of the catalyst after the oxygen and hydrogen evolution reactions was performed by XPS and showed the presence of a Co-II/Co-III oxidation state.
Keywords: cobalt; Electrochemistry; heterogeneous catalysis; Hydrogen; water splitting

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis

Potential- and time-dependent dynamic nature of an oxide-derived pdin nanocatalyst during electrochemical CO2 reduction - Bagchi, Debabrata; Sarkar, Shreya; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2022)
Electrochemical reduction of CO2 into valuable fuels and chemicals is a promising route of replacing fossil fuels by reducing CO2 emissions and minimizing its adverse effects on the climate. Tremendous efforts have been carried out for designing efficient catalyst materials to selectively produce the desired product in high yield from CO2 by the electrochemical process. In this work, a strategy is reported to enhance the electrochemical CO2 reduction reaction (ECO2RR) by constructing an interface between a metal-based alloy (PdIn) nanoparticle and an oxide (In2O3), which was synthesized by a facile solution method. The oxide-derived PdIn surface has shown excellent eCO(2)RR activity and enhanced CO selectivity with a Faradaic efficiency (FE) of 92.13% at -0.9 V (vs RHE). On the other hand, surface PdO formation due to charge transfer on the bare PdIn alloy reduces the CO2RR activity. With the support of in situ (EXAFS and IR) and ex situ (XPS, Raman) spectroscopic techniques, the optimum presence of the Pd-In-O interface has been identified as a crucial parameter for enhancing eCO(2)RR toward CO in a reducing atmosphere. The influence of eCO(2)RR duration is reported to affect the overall performance by switching the product selectivity from H-2 (from water reduction) to CO (from eCO(2)RR) on the oxide-derived alloy surface. This work also succeeded in the multifold enhancement of the current density by employing the gas diffusion electrode (GDE) and optimizing its process parameters in a flow cell configuration.
Keywords: CO2 reduction; Electrochemistry; heterostructure interface; in situ mechanism; nanocatalyst

Single-step synthesis of exfoliated Ti3C2Tx MXene through NaBF4/HCl etching as electrode material for asymmetric supercapacitor - Ghosh, Meena; Szunerits, Sabine; Cao, Ning; Kurungot, Sreekumar; Boukherroub, Rabah (ChemistrySelect, 2022)
Two-dimensional Ti3C2Tx MXene, derived from the parent Ti3AlC2 phase, is considered a promising electrode material for electrochemical energy storage applications. Ti3C2Tx MXene synthesis methods often employ concentrated hydrofluoric acid (HF), which is harsh, corrosive, and hazardous to the environment. Herein, we report the preparation of Ti3C2Tx MXene following a new synthetic route under a mild reaction condition comprising an aqueous solution of NaBF4 and HCl. This etching environment at a moderate temperature of 130 degrees C effectively removes the Al layer of the Ti3AlC2 precursor, assisted by the in situ formed HF in the reaction medium. Electron microscopy images of the as-prepared Ti3C2Tx (MX-130) reveal a partially exfoliated nanosheet-like morphology. The material displays a specific capacitance of 262 F g(-1) (three-electrode assembly, 1 A g(-1), -0.85 to -0.25 V vs. Hg/Hg2SO4) in 1 M H2SO4 electrolyte. The achieved specific capacitance is superior to that of Ti3C2Tx prepared via the common HF-treatment (25 F g(-1)). Additionally, the potential application of the optimized MXene as a negative electrode material is demonstrated in a quasi-solid-state RuO2|MX-130 asymmetric supercapacitor device.
Keywords: asymmetric supercapacitor; Electrochemistry; Fluoride salt etchant; Layered electrode materials; Transition metal carbides

Structure-tailored surface oxide on Cu-Ga intermetallics enhances CO2 reduction selectivity to methanol at ultralow potential - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C. (Advanced Materials, 2022)
Electrochemical CO2 reduction reaction (eCO(2)RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of -0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO(2)RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2O3, which is probed by in situ XAFS, quasi in situ powder X-ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope-labeling experiments in presence of (CO2)-C-13. Finally, to minimize the mass transport limitations and improve the overall eCO(2)RR performance, a poly(tetrafluoroethylene)-based gas diffusion electrode is used in the flow cell configuration.
Keywords: (2) reduction; CO; Electrochemistry; Methanol

Exploring FeSe2 and porous carbon composite as a cost-effective host for Al3+ in aqueous Aluminum ion batteries - Mirzapure, Vinay; Patrike, Apurva; Shelke, V, Manjusha (Electrochimica Acta, 2025)
Aluminum is a high-energy-density material with low cost, making rechargeable aluminum ion batteries (AIBs) a attractive alternative to alkali metal ion batteries. However, the practical development of aqueous AIBs is hindered by limited electrode. Herein, we report FeSe2-decorated porous nitrogen and sulfur-doped carbon spheres (FSPNSCS) as a cathode material for aqueous AIBs, with an emphasis on the reaction kinetics and electrochemical performance. FSPNSCS is synthesized through a hydrothermal approach, confirmed by comprehensive characterizations using X-ray Diffraction for crystalline structure validation and Scanning Electron Microscopy for analyzing composite morphology. Electrochemical properties and kinetics are probed using cyclic voltammetry and galvanostatic charge-discharge tests. Ex-situ XRD reveals a notable peak shift towards higher 2 theta values during discharge, indicating lattice contraction due to Al3+ insertion. Sulfur and nitrogen doping impart elasticity to the lattice structure, enhancing stability during cycling. Ex-situ XPS confirms Al3+ storage and minimal oxide formation, as further supported by microscopic elemental mapping with HRTEM. The FSPNSCS cathode achieves a reversible capacity of 60 mAh g- 1 at a current density of 200 mA g- 1. The system exhibits outstanding cycling stability, retaining over 90 % of its capacity at 500 mA g- 1 over 1000 cycles, highlighting its potential to advance aqueous AIBs for sustainable energy storage.
Keywords: Aqueous aluminum ion battery; cathode material; Electrochemistry; Transition metal selenide